(untitled) (Journal of the College of Basic Education, 2022)
Lactic acid production during growth of probiotic bacteria (L.acidophilus &Bifidobacterium sp.) in model MRSB media has been monitored using HPLC. HPLC evaluation showed that L.acidophilus achieved lactic acid concentration (44.6)%and Bifidobacterium achieved concentration (2.6)% (after 24 h of fermentation) .The acetic acid content was higher in MRS broth with Bifidobacterium sp. (4.1)% while the MRS broth with L.acidophilus nil from acetic acid .The inhibition activity of this probiotic bacteria filtrates was studied against some pathogenic bacteria included Proteus sp., Staphylococcus epidermidis, Pseudomonas aeruginosa ,Klebsiella sp. The results showed inhibition activity of both L.acidophilus &Bifidobacterium sp. filtrates against pathogen bacteria.